Non-Performing Loans and Operating Expenses Impact on Capital Adequacy Ratio - Estiasih, Soffia Pudji; Noerchoidah, Noerchoidah; Nurdina, Nurdina; Putra, Andhika Cahyono (Journal of Accounting Science, 2024)
General Background: Banks are pivotal to economic development, serving as financial intermediaries that facilitate capital flow between savers and borrowers. Their financial health is often assessed using ratios like the Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), and Operating Expenses to Operating Income (OEOI). Specific Background: The CAR indicates a bank's ability to withstand potential losses, making it a critical measure of financial stability. The relationship between NPL, OEOI, and CAR, with Return on Equity (ROE) as a moderating variable, remains underexplored, particularly in the context of Indonesian commercial banks. Knowledge Gap: Previous studies have inadequately addressed how ROE moderates the effects of NPL and OEOI on CAR. Aims: This study aims to examine the interactions between NPL and OEOI on CAR, moderated by ROE, using data from 30 commercial banks listed on the Indonesian Stock Exchange from 2018 to 2020. Results: The findings reveal that NPL significantly negatively impacts CAR, while OEOI's effect is negative but insignificant. ROE moderates the impact of OEOI on CAR significantly but not NPL. Novelty: This study introduces ROE as a moderating variable, providing a nuanced understanding of its differential effects on CAR in the Indonesian banking sector. Implications: The results offer practical insights for bank management to optimize financial performance and contribute theoretically to the literature on banking stability and profitability. These findings can inform future research and decision-making in the financial industry.